The Experiment of Dielectric Frequency Response of Serviced Aged Distribution Transformer - Purichaya Posrimahapoch; Noppadol Maneerat; Danaiwat Daengdee; Siwakorn Jeenmuang; Pittaya Pannil; Norasage Pattanadech (My University, 2024)
Outdoor Distribution Transformers typically encounter random environments and affect moisture in any ingress ways, e.g., defective breathing, oil leakage, or human error during internal inspection, etc. Such moisture is a very important enemy of the insulation integrity of the transformer. It may cause the failure of the transformer eventually. Therefore, the condition of the transformer insulation needs to be monitored. Dielectric Frequency Response (DFR), also known as Frequency Domain Spectroscopy (FDS), and Polarization and Depolarization Current (PDC) are nondestructive tests providing efficient diagnostic for transformer insulation. The test results can be used to estimate moisture content and oil conductivity. In this paper, the dielectric investigation of a 315 kVA, 22 kV serviced aged distribution transformers, which have been retired for 6 months after being utilized for more than 20 years, was conducted. The experiment results of the DFR and the PDC tests including the investigated mineral oil characteristics (i.e., oil breakdown voltage, moisture content, and tan delta) are reported and analyzed. They should be useful to understand the condition of the transformers.
Keywords: Power Transformer Diagnostics and Insulation; Advanced Computational Techniques and Applications; Magnetic Properties and Applications